2012
DOI: 10.1017/s0890060412000042
|View full text |Cite
|
Sign up to set email alerts
|

Spatial grammar implementation: From theory to useable software

Abstract: Currently available computer-aided design tools provide strong support for the later stages of product development processes where the structure and shape of the design have been fixed. Support for earlier stages of product development, when both the structure and shape of the design are still fluid, demands conceptual design tools that support designers' ways of thinking and working, and enhance creativity, for example, by offering design alternatives, difficult or not, possible without the use of such tools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 16 publications
(33 reference statements)
0
36
0
1
Order By: Relevance
“…Descriptions of concrete applications are less common but do occur, for example, in the shape computation literature (Stiny 2008). However, methods to enable the robust implementation of embedding for use in real-world applications remains an open research issue (McKay et al 2012). The ultimate goal of the research reported in this paper is to explore the use of embedding as a way of allowing engineers to associate multiple design structures with a given design, so that they may be used as and when needed.…”
Section: Underlying Theory For Embeddingmentioning
confidence: 99%
“…Descriptions of concrete applications are less common but do occur, for example, in the shape computation literature (Stiny 2008). However, methods to enable the robust implementation of embedding for use in real-world applications remains an open research issue (McKay et al 2012). The ultimate goal of the research reported in this paper is to explore the use of embedding as a way of allowing engineers to associate multiple design structures with a given design, so that they may be used as and when needed.…”
Section: Underlying Theory For Embeddingmentioning
confidence: 99%
“…Computer implementation of shape grammars with shape emergence is challenging (Chase, 2010; McKay et al, 2012; Yue & Krishnamurti, 2013). Five shape grammar implementations that support shape emergence are considered here (Table 1).…”
Section: Background and Related Workmentioning
confidence: 99%
“…The first SG interpreter is the one of Gips (1975), and since then several interpreters have been developed to address particular features, namely: subshape recognition (Krishnamurti, 1980), 3D shapes (Earl, 1986), intuitive visual interface (Tapia, 1999), curves (Jowers & Earl, 2011), parametric rules (Grasl & Economou, 2013), and display of design alternatives (Strobbe et al, 2015). However, there is no SG interpreter that fully supports all the features, and some features are clearly underdeveloped, for example, the capability to express descriptions (McKay et al, 2012). These limitations make it difficult to implement a complex SG that requires large amounts of information for domain-specific design tasks (Li, 2002).…”
Section: Sg Implementationsmentioning
confidence: 99%